CLIMATE AND MENOPAUSE: NURSING ASSISTANCE TO WOMEN’S HEALTH IN PRIMARY CARE - Melise Pereira de Sousa, Maria; dos Santos Lima, Nathalia; Eduarda Almeida de Souza, Cicera; Caroline de Souza, Anne; Silva Oliveira, Geane (Health and Society, 2023)
Climacteric and menopause is defined by the World Health Organization (WHO) as a biological phase of a woman’s life and not a pathological process. After the onset of menarche (beginning of the first menstrual cycle), the climacteric is the second most striking cycle in female life, characterized by metabolic and hormonal changes that bring changes involving the psychosocial context. It is a time of transition from the fertile period to the non-reproductive phase. This stage is due to a natural decline in female reproductive hormones, luteinizing hormone (LH) and follicle stimulating hormone (FSH). In addition, the predisposing signs and symptoms of climacteric are when the ovaries begin to produce less estrogen and progesterone, which are hormones that regulate menstruation, and fertility progressively decreases. Faced with this whole situation that we seek to uncover, this research was reformulated based on the following guiding question: What assistance can the primary care nursing professional offer to women during the climacteric and menopause period? This study is an integrative literature review, which was carried out between the months of August and September 2022, from secondary sources, through a bibliographical survey in banks and scientific databases: SCIELO, LILACS and BDENF. The following descriptors were used, integrated using the Boolean operator AND: “Menopause”, “Climate”, “Nursing” and “Basic Health Unit”. The inclusion criteria defined for the selection of articles were: scientific articles freely available in Portuguese and published in the last 5 years. With regard to the exclusion criteria, there are: monographs, theses and dissertations. In the analysis of this study, the main information regarding the assistance of nursing professionals for women in the climacteric and menopause phase were highlighted. In view of this, the importance of interventions aimed at health education strategies was verified. Actions must start even before the woman enters the climacteric phase, as she must know all the information necessary to face this period with more knowledge. Care for climacteric women in primary health care has particularities that require professional training, legitimacy and patient awareness. Therefore, the main actions that need to be carried out with this public are to assess and identify symptoms, assess risks to women’s health, identify pre-existing comorbidities and provide psychological support when necessary.